Penerapan Markerless Augmented Reality pada E-Katalog Variasi Mobil Menggunakan Metode Natural Feature Tracking - Stevens Khouw; Edy (bit-Tech, 2023)
Information technology is widely used by business people in promoting the products and services they sell, this is very important especially for businesses that sell products that are not common, for example car variations. Car variation business is already widely found in various regions in Indonesia, but the car variation business has a relatively small and specialized market. The main cause is the lack of promotion of product knowledge to the public and the lack of interesting and practical forms of promotional media that make car variation products rarely seen by vehicle owners. Therefore, in this study, attempted on the application of augmented reality technology into the e-catalog application of car variations using the natural feature tracking method to help the visual augmentation process of car variation products that want to be seen as a form of promotional media for car variation products in general, the e-catalog itself were made using unity engine. From this research, the results obtained are: the application of augmented reality was successfully carried out on the Android e-catalog application, the attractiveness of the application display with a good indicator of 100%, the attractiveness of augmented reality with a percentage of 88.9% on good indicators and the appropriateness of application development with a percentage of 100% on good indicators, these result are obtained from questionnaires that are distributed to both coworker and random users as sample.